Impact of Continued Mailed Fecal Tests in the Patient-Centered Medical Home: Year 3 of the Systems of Support to Increase Colon Cancer Screening and Follow-Up Randomized Trial - Green, Beverly B. (Cancer, 2015)
BACKGROUND: The current study was conducted to determine the effect of continuing a centralized fecal occult blood test (FOBT) mailed program on screening adherence. METHODS: A patient-level randomized controlled trial was conducted in 21 patient-centered medical home primary care clinics between January 2010 and November 2012. A total of 2208 patients ranging in age from 52 to 75 years in a substudy of the Systems of Support to Increase Colon Cancer Screening and Follow-Up (SOS) trial were randomized at year 3 to continued automated interventions (Continued group), which included mailed information regarding colorectal cancer (CRC) screening choices, and were mailed stool kit tests or to a group in which interventions were stopped (Stopped group). The main outcomes and measures were the completion of CRC screening in year 3 and by subgroup characteristics, respectively. RESULTS: Adherence to CRC screening in year 3 was found to be significantly higher in patients in the Continued group compared with those in the Stopped group (53.3% vs 37.3%; adjusted net difference, 15.6% [P<.001]). This difference was entirely due to greater completion of FOBT (adjusted net difference, 18.0% [P<.001]). Year 3 CRC screening rates were highest in patients in the Continued group completing FOBT in both years 1 and 2 (77.2%), followed by patients completing only 1 FOBT in 1 of the 2 years (44.6%), with low rates of CRC testing reported among patients not completing any FOBT within the first 2 years (18.1%). CONCLUSIONS: A centralized mailed FOBT CRC screening program continued to be more effective than patient-centered medical home usual-care interventions, but only for those patients who had previously completed FOBT testing. Research is needed regarding how to engage patients not completing CRC testing after being mailed at least 2 rounds of FOBT tests.